Comments on Inadequacy of Draft Environmental Assessment/environmental Impact Report for Land Acquisition and Airport Development at Oxnard Airport - Richard J. Maggio:::::: (1999)
Correspondence discussing the final environmental report on Oxnard Airport and provides new information that had recently become available.